2015
DOI: 10.1016/j.ijsu.2015.08.074
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese randomized prospective trial of floppy Nissen and Toupet fundoplication for gastroesophageal disease

Abstract: LTF seems to be as safe and effective on the long-term as LNF, but with a lower incidence of postoperative dysphagia (ChiCTR-TRC-13003945).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…Mild dysphagia is relatively usual in the direct postoperative phase and improves as the mucosal edema and/or hematoma of the wrap subside. Instead, PD is infrequent, but occurs up to 20% and represents a challenge in further treatment [4, 9, 10]. It has been shown that the presence of preoperative dysphagia and IEM, certain preoperative LES characteristics and surgical technique have an influence in the development of PD [9, 10, 25].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mild dysphagia is relatively usual in the direct postoperative phase and improves as the mucosal edema and/or hematoma of the wrap subside. Instead, PD is infrequent, but occurs up to 20% and represents a challenge in further treatment [4, 9, 10]. It has been shown that the presence of preoperative dysphagia and IEM, certain preoperative LES characteristics and surgical technique have an influence in the development of PD [9, 10, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no clear consensus on the ideal fundoplication, lower PD rates have been observed in patients who underwent TF instead of LNF [8, 10, 15]. Furthermore, TF is the current treatment of choice in patients with IEM, in order to avoid PD [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations